Hydration Status of Patients Dialyzed with Biocompatible Peritoneal Dialysis Fluids - Lichodziejewska-Niemierko, Monika (Perit Dial Int, 2016)
♦ BACKGROUND: Biocompatible fluids for peritoneal dialysis (PD) have been introduced to improve dialysis and patient outcome in end-stage renal disease. However, their impact on hydration status (HS), residual renal function (RRF), and dialysis adequacy has been a matter of debate. The aim of the study was to evaluate the influence of a biocompatible dialysis fluid on the HS of prevalent PD patients. ♦ METHODS: The study population consisted of 18 prevalent PD subjects, treated with standard dialysis fluids. At baseline, 9 patients were switched to a biocompatible solution, low in glucose degradation products (GDPs) (Balance; Fresenius Medical Care, Bad Homburg, Germany). Hydration status was assessed through clinical evaluation, laboratory parameters, echocardiography, and bioimpedance spectroscopy over a 24-month observation period. ♦ RESULTS: During the study period, urine volume decreased similarly in both groups. At the end of the evaluation, there were also no differences in clinical (body weight, edema, blood pressure), laboratory (N-terminal pro-brain natriuretic peptide, NTproBNP), or echocardiography determinants of HS. However, dialysis ultrafiltration decreased in the low-GDP group and, at the end of the study, equaled 929 ± 404 mL, compared with 1,317 ± 363 mL in the standard-fluid subjects (p = 0.06). Hydration status assessed by bioimpedance spectroscopy was +3.64 ± 2.08 L in the low-GDP patients and +1.47 ± 1.61 L in the controls (p = 0.03). ♦ CONCLUSIONS: The use of a low-GDP biocompatible dialysis fluid was associated with a tendency to overhydration, probably due to diminished ultrafiltration in prevalent PD patients.